Penggunaan Konjungsi sebagai Unsur Kohesi Pada Berita Utama Surat Kabar Padang Ekspres - Suci Raufi Alkarima; Amril Amir (PT. ALHAFI BERKAH INDONESIA, 2023)
Errors in the use of conjunctions are still found in the headlines of the Padang Ekspres newspaper. The purpose of this study is to determine the type and quality of conjunctions used in the headlines of the Padang Ekspres newspaper. So, the method used is descriptive method. So that this study resulted in the use of conjunctions in the headlines of the Padang Ekspres newspaper having an accuracy of 90.4%. The implications of research on learning Indonesian in odd semester class VIII.